SPE California Regional Meeting 1986
DOI: 10.2118/15087-ms
|View full text |Cite
|
Sign up to set email alerts
|

Some Parameters Influencing the Formation and Propagation of Foams in Porous Media

Abstract: oil-in-placeremains bypassed either in the deepeat regions of the resexvoir (gravityoverride case) orExperiments were run to Investigatethe effect in the lower permeabilityzones (channelingcaae). of surfactant concentration, injection rate, foam quality, oil saturation, and rock absolute perme-Because of the high fuel coat to generate the ability on the formation and propagation of foama injected steam, research efforts by the oil indusin Berea aandstoneaand Ottawa sandpacks. try have recently been directed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 8 publications
5
77
3
Order By: Relevance
“…saturation, the relative permeability to the liquid is the same as that in two-phase flow of immiscible Newtonian fluids, independent of the presence of a discontinuous foam phase. Essentially all investigations of foam flow in porous media confirm this observation [1,3,5,[13][14][15].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…saturation, the relative permeability to the liquid is the same as that in two-phase flow of immiscible Newtonian fluids, independent of the presence of a discontinuous foam phase. Essentially all investigations of foam flow in porous media confirm this observation [1,3,5,[13][14][15].…”
Section: Discussionsupporting
confidence: 57%
“…Micromodcl studies [9,[16][17][18] and core effluent observations [15,19] of texture indicate that the bubble size distribution exhibits a wide spread. Bubbles can be significantly smaller or larger than pore bodies but generally they arc (In the order of one to several pore body volumes (see, for example, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, effect of foam on gas mobility can be interpreted as an increase in gas apparent viscosity or as a decrease in gas relative permeability. [14] Figure 2.7 shows the results from an experimental study [4] in which it was concluded that gas permeability was reduced significantly since lamellae were stabilized in the presence of surfactant (the top and bottom curves). However, the middle curve does not show an increase in gas saturation due to trapping in both cases.…”
Section: Effect Of Foam On Gas Mobilitymentioning
confidence: 99%
“…Many published studies [76][77][78][79][80][81] confirmed that the presence of foam did not affect the wettingphase relative permeability. Darcy's law can be applied to calculate water relative permeability.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 88%